Determination of Factors Affecting “Level of Dependency on Social Aid” of Household Living in Rural Area: Iğdır Province Rural Area Example, Türkiye - Osman Doğan Bulut; Cengiz Sayın (Journal of Agricultural Sciences)
Fighting against poverty has become an increasing topic both at international and national levels. In this context, social policy programmes and particularly the implementation and delivery of social aid programs are one of key policy tools widely used in many countries to alleviate poverty and reduce hunger. Assessing the Aid Dependency Rate (ADR) of the beneficiaries is of great importance to achieve the goal of designed and delivered social assistance programs. Therefore, this study determines beneficiaries’ level of dependency on social aid and the underlying factors. Primary data were collected through face-to-face survey from 210 households actively beneficiaries of public social aid selected by use of snowball sampling. Additionally, ordinal logistic regression analysis was conducted to determine the factors affecting the level of need of households for public social aid. The findings showed that 46.7% of households were in low level dependency on social aid, 28.6% in intermediate level, and 24.8% in high level. Besides, the results of the ordinary logistic regression analysis revealed that the marital status, employment status of the household and the group of delivered social aid were significant factors affecting level of need for social aid (P<0.05). Also, it shows that the odd ratio of household of being in high level increases 264.25 times if there is not any working individual compared to households with two or more working individuals (P<0.01) whereas this ratio decreases to 3.71 (P<0.05) in households by only one individual working. The study concludes that the presence of even one working individual is of great importance in order to prevent the household's dependence on social aid in high level. Consequently, designing social aid programs that consider the mentioned factors would help to fight against poverty.